2018
DOI: 10.1039/c8fo00763b
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane ameliorates glucose intolerance in obese mice via the upregulation of the insulin signaling pathway

Abstract: Sulforaphane (SFN) is a dietary component with multiple bioactivities; however, its role in obesity-related metabolic derangement remains unclear. Here, the effect of SFN on the glucose intolerance of obese mice and the underlying mechanism were determined. C57B/6J male mice were randomly divided into two groups, having free access to water and a normal-fat diet (ND, n = 6) or a high-fat diet (HFD, n = 33) for 8 weeks; thereafter twelve mice having the greatest weight gain among the HFD-fed mice were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
5
29
0
Order By: Relevance
“…Sulforaphane is a compound with multiple bioactivities such as antidiabetic and antioxidant effects. Sulforaphane could improve glucose tolerance through up-regulation of insulin signaling involving IRS-1/Akt/GLUT 4 pathway in muscle( Xu et al, 2018 ). Sulforaphane also attenuated glucose intolerance and affected GLUT3 expression in the cerebral cortex and hypothalamus( Souza et al, 2013 ).…”
Section: Repurposing Of Anti-diabetic Agents As a Potential Treatment Targeting Cognitive Function In Ad And Schizophreniamentioning
confidence: 99%
“…Sulforaphane is a compound with multiple bioactivities such as antidiabetic and antioxidant effects. Sulforaphane could improve glucose tolerance through up-regulation of insulin signaling involving IRS-1/Akt/GLUT 4 pathway in muscle( Xu et al, 2018 ). Sulforaphane also attenuated glucose intolerance and affected GLUT3 expression in the cerebral cortex and hypothalamus( Souza et al, 2013 ).…”
Section: Repurposing Of Anti-diabetic Agents As a Potential Treatment Targeting Cognitive Function In Ad And Schizophreniamentioning
confidence: 99%
“…However, Ernst et al [ 9 ] reported that treatment with sulforaphane and other ITCs, such as allyl isothiocyanate, results in comparative levels of phase 2 enzymes including γ -glutamyl cysteine synthetase and antioxidant enzymes via an Nrf2-dependent signal transduction pathway in cultured cells and in vivo experiments. Conversely, Valli et al [ 10 ] and Xu et al [ 11 ] demonstrated that sulforaphane-treated obese mice exhibited significantly increased IRS-1 protein levels and marked Akt/PKB activation. Comparison of IRS-1 upregulation by sulforaphane and other ITCs, including allyl isothiocyanate, will require additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Allyl isothiocyanate (Figure 1) is known to be responsible for the characteristic pungent aroma of some cruciferous vegetables, including radishes and horse radishes. Both of these are naturally occurring ITCs repress adipogenesis [9][10][11]. However, with the exception of their ITC moieties, the pharmacological differences caused by their distinct structures-the sulfinyl groups in sulforaphane and the allyl groups in allyl isothiocyanate-have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Brassica crops (e.g., cabbage, broccoli, cauliflower, kale, collards, and brussel sprouts) contain chemicals that release sulforaphane upon hydrolysis. Sulphoraphane has been shown to help reduce obesity (131), improve glucose tolerance (132), and restore leptin sensitivity in high fat-sucrose diet fed obese mice (133). Sulforaphane functions by protecting against oxidative stress via activation of the Nrf2-ARE pathway in multiple tissues (134, 135).…”
Section: Strategies To Mitigate the Impact Of Environmental Mdcsmentioning
confidence: 99%